2002
DOI: 10.1073/pnas.212645999
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic intervention in experimental allergic encephalomyelitis by administration of uric acid precursors

Abstract: Uric acid (UA) is a purine metabolite that selectively inhibits peroxynitrite-mediated reactions implicated in the pathogenesis of multiple sclerosis (MS) and other neurodegenerative diseases. Serum UA levels are inversely associated with the incidence of MS in humans because MS patients have low serum UA levels and individuals with hyperuricemia (gout) rarely develop the disease. Moreover, the administration of UA is therapeutic in experimental allergic encephalomyelitis (EAE), an animal model of MS. Thus, ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
92
2
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(98 citation statements)
references
References 38 publications
3
92
2
1
Order By: Relevance
“…Uric acid, a competitive inhibitor of tyrosine nitration by peroxynitrite (Robinson et al, 2004), and FeTPPS, a decomposition catalyst of peroxynitrite , have been shown to be protective in the EAE animal models of MS (Hooper et al, 1998;Cross et al, 2000;Hooper et al, 2000;Bolton et al, 2008). These results are consistent with the findings that patients with MS and hyperuricemia are mutually exclusive (Spitsin et al, 2001;Scott et al, 2002). Although several studies suggest that inhibitors of iNOS ameliorate EAE (Brenner et al, 1997;Hooper et al, 1997), mice with targeted gene deletion of iNOS (iNOSϪ/Ϫ) are found to have an in-creased disease severity (Fenyk-Melody et al, 1998;Sahrbacher et al, 1998).…”
supporting
confidence: 82%
See 1 more Smart Citation
“…Uric acid, a competitive inhibitor of tyrosine nitration by peroxynitrite (Robinson et al, 2004), and FeTPPS, a decomposition catalyst of peroxynitrite , have been shown to be protective in the EAE animal models of MS (Hooper et al, 1998;Cross et al, 2000;Hooper et al, 2000;Bolton et al, 2008). These results are consistent with the findings that patients with MS and hyperuricemia are mutually exclusive (Spitsin et al, 2001;Scott et al, 2002). Although several studies suggest that inhibitors of iNOS ameliorate EAE (Brenner et al, 1997;Hooper et al, 1997), mice with targeted gene deletion of iNOS (iNOSϪ/Ϫ) are found to have an in-creased disease severity (Fenyk-Melody et al, 1998;Sahrbacher et al, 1998).…”
supporting
confidence: 82%
“…A growing body of evidence has shown that peroxynitrite, a reaction product between nitric oxide and superoxide near a diffusion-controlled rate, plays a pathogenic role in MS and the animal counterpart, EAE (Cross et al, 1997(Cross et al, , 1998Hooper et al, 1998Hooper et al, , 2000Scott et al, 2002;Bolton et al, 2008). Although the scavengers or the decomposition catalysts of peroxynitrite are consistently shown to ameliorate EAE (Cross et al, 2000;Hooper et al, 2000;Scott et al, 2002;Bolton et al, 2008), pharmacological inhibitors or genetic deletion of iNOS and NADPH oxidase, the primary enzymes for nitric oxide and superoxide production in reactive microglia or macrophages, often produce opposing results, with both beneficial and deleterious effects observed (Brenner et al, 1997;Hooper et al, 1997;Fenyk-Melody et al, 1998;Sahrbacher et al, 1998;van der Veen et al, 2000van der Veen et al, , 2004Hultqvist et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In C57BL/6 mice, immunization with myelin oligodendrocyte glycoprotein (MOG) induces a progressive disease, which is characterized by demyelination and inflammation in the CNS [9,10]. Although considerable progress has been made in understanding the genetic susceptibility and pathogenesis of this disease, there is still no uniformly effective treatment strategy [15,18]. The enzymatic digestion of the blood brain barrier and myelin protein by serine proteases is known to contribute to the development and progression of MS and EAE [1,12,19].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to MS, EAE involves the accumulation of inflammatory cells expressing iNOS (NOS-2) in CNS tissue lesions (14,15). Evidence suggests that peroxynitrite, a downstream product of iNOS, can play an important role in the pathogenesis of MS and EAE (14,(16)(17)(18). However, mice lacking iNOS remain highly susceptible to the induction of EAE (19).…”
mentioning
confidence: 99%